Performance Characteristics of Indigenous Turkeys Fed Indomie Waste Based Diets - Ironkwe, Monica Ogochukwu; Esonu, Babington Onyemachi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. This study evaluated the performance of turkey poults fed indomie waste based diet. A total of ninety six (96) local strain turkey poults were allotted to four dietary treatment in which indomie waste was used to replace maize at 0, 33.33, 66.67 and 100% levels, representing one to four treatments respectively. Each treatment was replicated three times with eight poults per replicate. The study which lasted for eight weeks was a completely randomized design experiment. Results showed that indomie waste significantly increased the average weight gain and improved feed conversion ratio. The cost of feed per kg decreased with increasing levels of indomie waste in the diet. The lowest cost was obtained at 66.67% inclusion level. It was evident that indomie waste could be incorporated into the diet of local strain turkey poults up to 66.67% level without any deleterious effect on the performance of the turkeys. There is also a concomitant reduction in feed cost per kg weight gain. Key words: performance, characteristics, indigenous, turkey, indomie waste Abstrak. Penelitian ini mengevaluasi performa peternakan kalkun yang diberi pakan berbahan baku limbah indomie. Sejumlah 96 kalkun diberi empat pakan percobaan menggunakan limbah indomie untuk menggantikan tepung jagung pada level 0, 33.33, 66.67 dan 100%. Setiap percobaan diulang 3 kali menggunakan 8 kalkun. Penelitian selama delapan minggu menggunakan rancangan acak lengkap. Hasil penelitian menunjukkan bahwa limbah indomie secara nyata meningkatkan kenaikan bobot rata-rata dan rasio konversi pakan. Biaya pakan per kg menurun seiring meningkatnya asupan limbah indomie. Biaya terendah diperoleh pada tingkat 66.67%. Limbah indomie dapat digunakan pada pakan kalkun lokal hingga 66.67% tanpa ada efek negatif pada performa kalkun. Biaya pakan per kg bobot badan juga menurun. Kata kunci: performa, karakteristik, ternak lokal, kalkun, limbah indomie